Treatment response and drug retention rates in 24 195 biologic-naïve patients with axial spondyloarthritis initiating TNFi treatment: routine care data from 12 registries in the EuroSpA collaboration. Issue 11 (November 2019) - Ørnbjerg, Lykke Midtbøll; Brahe, Cecilie Heegaard; Askling, Johan; Ciurea, Adrian; Mann, Herman; Onen, Fatos; Kristianslund, Eirik Klami; Nordström, Dan; Santos, Maria Jose; Codreanu, Catalin; Gómez-Reino, Juan; Rotar, Ziga; et al.
Abstract : Objective: To study drug retention and response rates in patients with axial spondyloarthritis (axSpA) initiating a first tumour necrosis factor inhibitor (TNFi). Methods: Data from 12 European registries, prospectively collected in routine care, were pooled. TNFi retention rates (Kaplan-Meier statistics), Ankylosing Spondylitis Disease Activity Score (ASDAS) Inactive disease (<1.3), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) <40 mm and Assessment of SpondyloArthritis International Society responses (ASAS 20/40) were assessed at 6, 12 and 24 months. Results: A first TNFi was initiated in 24 195 axSpA patients. Heterogeneity of baseline characteristics between registries was observed. Twelve-month retention was 80% (95% CI 79% to 80%), ranging from 71% to 94% across registries. At 6 months, ASDAS Inactive disease/BASDAI<40 rates were 33%/72% (LUNDEX-adjusted: 27%/59%), ASAS 20/40 response rates 64%/49% (LUNDEX-adjusted 52%/40%). In patients initiating first TNFi after 2009, 6097 patients was registered to fulfil ASAS criteria for axSpA, 2935 was registered to fulfil modified New York Criteria for Ankylosing Spondylitis and 1178 patients was registered as having non-radiographic axSpA. In nr-axSpA patients, we observed lower 12-month retention rates (73% (70%–76%)) and lower 6-month LUNDEX adjusted response rates (ASDAS Inactive disease/BASDAI40 20%/50%, ASAS 20/40 45%/33%). For patients initiating first TNFi after 2014, 12-month retention rate, but not 6-month response rate, was numerically higher compared with patients initiating TNFi in 2009–2014. Conclusion: A large European database of patients with axSpA initiating a first TNFi treatment in routine care, demonstrated that 27% of patients achieved ASDAS inactive disease after 6 months, while 59% achieved BASDAI <40. Four of five patients continued treatment after 1 year.